2020
DOI: 10.1002/mbo3.1108
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of microbiota across different intestinal tract segments of a stranded dwarf minke whale, Balaenoptera acutorostrata

Abstract: Animal digestive tracts are complex microecosystems composed of host cells and intestinal microbiota (Backhed, 2005). Their symbiotic relationship not only influences host metabolism, energy production, growth, and immunity but also underlies several pathological conditions (Flint, Scott, Louis, & Duncan, 2012; Malmuthuge, Li, Goonewardene, Oba, & Guan, 2013). Marine mammals are important microbial reservoirs thanks to their constant body temperature and large sizes (Higgins, 2000), and in recent years, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
3
7
0
Order By: Relevance
“…Previous limited studies showed that the stomach harbored high microbial diversity, and for the intestinal tract, the posterior compartment could be more suitable for microbial colonization across cetaceans and other animal species (e.g. Wan et al 2018;Tian et al 2020). Our results are consistent with those views.…”
Section: Diversity Of the Gut Microbiomes In The Short-finned Pilot Whalessupporting
confidence: 91%
See 1 more Smart Citation
“…Previous limited studies showed that the stomach harbored high microbial diversity, and for the intestinal tract, the posterior compartment could be more suitable for microbial colonization across cetaceans and other animal species (e.g. Wan et al 2018;Tian et al 2020). Our results are consistent with those views.…”
Section: Diversity Of the Gut Microbiomes In The Short-finned Pilot Whalessupporting
confidence: 91%
“…Studies on the microbial diversity and composition in the gastrointestinal tracts of cetaceans are very few. To our knowledge, only 3 papers investigated the microbial communities in different regions of the gastrointestinal tracts in cetaceans (Wan et al 2018(Wan et al , 2020Tian et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Though broad, the available data and research for these species has little depth; but with the constant improvement of molecular methods and new studies being produced, greater depth will be achieved in time. The further removed from humans, the less is known about a particular species [5,6,7,17,18]. Exploratory studies serve to deepen already available knowledge and con rm trends unearthed by previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the gut's in uence on health and general wellbeing it has been subject to a great amount of study in other species and with more research becoming available every year it has become easier to discern the overarching mechanics of the triploblastic gut. However, the ner details involved in said functions within separate animal species remain opaque with omissions and exclusions being a rule more often than an exception; studies purporting to cover an under or never before examined aspect of a certain species' microbiome have become more and more common [5,6,7,8,9 ] With the adoption of molecular biological techniques, insight into the composition, interactions, and biproducts of microbial communities has become more widely available, allowing for closer inspection and observation of these previously inaccessible machinations [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sanders et al [ 12 ] investigated the microbial diversity and function of gut microbiomes in baleen whales feces and found them harbored unique gut microbiomes whereas still kept a functional capacity similar to that of both carnivores and herbivores; (2) fecal samples from human cared animals, such as studies on belugas ( Delphinapterus leucas ), Pacific white-sided dolphins ( Lagenorhynchus obliquidens ) and common bottlenose dolphins ( Tursiops truncatus ) [ 13 , 14 ], and Yangtze finless porpoises ( Neophocaena phocaenoides asiaeorientalis ) [ 15 ]; and (3) from dead, stranded animals. A few of studies sequenced along the gastrointestinal tracts of stranded cetaceans to investigate the distribution of microorganisms in different gut regions [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%